A zinc ion battery electrolyte and its preparation method and application
By adding six methylticoramine to the electrolytes of zinc ion batteries, the interface molecular layer is constructed, the problem of zinc negative corrosion corrosion and chief crystal growth is solved, and the electrochemical properties and safety of zinc ion batteries are significantly improved.
Patent Information
- Application Number
- CN202211519302.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-11-30
AI Technical Summary
Corrosion of zinc negative electrode and dendrites in zinc ion batteries leads to poor battery circulation performance, low Coulomb efficiency and insufficient safety performance, hindering the commercialization process of zinc ion batteries.
By adding six methyltamine to zinc salt to form a modified electrolyte, it is easy to adsorb on the metal surface and combined with the metal ion, so as to build the interface molecular layer on the in original position of the surface of the zinc. Stable zinc negative.
Effectively suppress the growth of zinc branch crystals, prevent zinc foil from contact with water, reduce hydrogen analysis side effects, and prevent zinc foil corrosion, thereby improving the cycle performance of zinc ion batteries, Kuron efficiency and safety performance.
Smart Images

Figure CN115799664B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytes, and in particular to a zinc ion battery electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries play a vital role in the energy field of modern society due to their advantages such as high energy density, long cycle life and good cycle performance. However, on the one hand, the scarcity of lithium resources makes it difficult for lithium-ion batteries to meet the huge demand of the future market; on the other hand, the dendrite problem of lithium negative electrode will induce battery short circuit, cause combustion and explosion of organic electrolyte, and have poor safety performance. Therefore, in recent years, researchers have been committed to the research and development of lithium negative electrode modification and high-safety organic electrolytes on the one hand, and on the other hand, researchers have also focused on the research and development of aqueous secondary batteries with abundant raw materials on the earth and higher safety.
[0003] Aqueous metal-ion batteries are ideal for large-scale energy storage due to their high safety and low cost. Compared with other metals, metallic zinc has attracted widespread attention due to its high natural abundance, high theoretical weight / volume specific capacity, and low redox potential. In addition, due to the uneven zinc plating on the surface of the zinc negative electrode, the corrosion of the metallic zinc negative electrode and the uncontrollable dendrite growth during repeated charge and discharge will seriously reduce the battery's cycle performance, coulombic efficiency and even safety performance, greatly hindering the commercialization of zinc-ion batteries. Therefore, inhibiting the formation of dendrites is of great significance to the practical application of aqueous zinc-ion batteries.
[0004] The present invention starts from the perspective of electrolyte modification, by adding hexamethylenetetramine to zinc salt, utilizing its large electronegativity, easy adsorption on the metal surface and complexing with metal ions, thereby in-situ constructing an interface molecular layer on the surface of the zinc negative electrode to stabilize the zinc negative electrode. On the one hand, the interface molecular film can regulate the uniform deposition of zinc ions and inhibit the growth of zinc dendrites; on the other hand, it can prevent the zinc foil from further contacting with water, changing the coordination environment of zinc ions, thereby inhibiting the occurrence of hydrogen evolution side reactions during the charge and discharge process, and preventing the zinc foil from being corroded. Summary of the invention
[0005] In view of this, the present invention provides a zinc ion battery electrolyte and a preparation method and application thereof, which can effectively overcome the corrosion of the metal zinc negative electrode and the uncontrollable dendrite growth leading to poor battery cycle performance, low coulombic efficiency and even safety performance.
[0006] In order to achieve the above technical objectives, the technical solutions adopted in this application are as follows:
[0007] In a first aspect, the present invention provides a zinc ion battery electrolyte composition comprising zinc sulfate and hexamethylenetetramine.
[0008] In a second aspect, the present invention provides a zinc ion battery electrolyte comprising the above composition and a solvent.
[0009] Furthermore, in the electrolyte, the final concentration of zinc sulfate is 1-2 mol / L, and the final concentration of hexamethylenetetramine is 0.5-4 mg / mL.
[0010] Preferably, in the electrolyte, the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 0.5-2 mg / mL.
[0011] More preferably, in the electrolyte, the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 1 mg / mL.
[0012] Furthermore, the solvent is water.
[0013] In a third aspect, the present invention provides a method for preparing the above-mentioned zinc ion battery electrolyte, comprising:
[0014] A zinc sulfate solution of a certain concentration is prepared using a solvent;
[0015] Add hexamethylenetetramine and mix until completely dissolved.
[0016] In a fourth aspect, the present invention provides the use of the above zinc ion battery electrolyte in the preparation of a zinc ion battery.
[0017] In a fifth aspect, the present invention provides a zinc ion battery comprising the above-mentioned electrolyte.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention forms a modified electrolyte by compounding hexamethylenetetramine with a zinc salt, which can overcome the problems of poor cycle performance, low coulombic efficiency and even safety performance of the battery caused by corrosion of the metal zinc negative electrode and uncontrollable dendrite growth. Experiments have shown that the zinc ion battery prepared by using the electrolyte of the present invention has obvious improvements in electrochemical properties such as cycle performance and rate performance compared with the conventional zinc ion battery given in the comparative example of the specific embodiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0021] Figure 1 It is a graph showing the cycle performance test results of the four Zn||Zn symmetric batteries in Comparative Example 2 and Examples 1-3.
[0022] Figure 2Graph showing the cycle performance test results of the Zn||Zn symmetric battery at different current densities in Comparative Example 2 and Example 2, wherein: Figure 2-1 1mA cm -2 , 1mAh cm -2 Cyclic performance test results diagram, Figure 2-2 2mA cm -2 , 2mAhcm -2 Cyclic performance test results diagram, Figure 2-3 4mA cm -2 , 4mAh cm -2 Cyclic performance test results diagram.
[0023] Figure 3 : Corrosion current density of the four Zn||Zn symmetric cells in Comparative Example 5 and Examples 4-6.
[0024] Figure 4 It is the AC impedance diagram of the four Zn||Zn symmetric batteries in Comparative Example 2 and Examples 1-3.
[0025] Figure 5 It is a diagram of the hydrogen evolution reaction of the four Zn||Zn symmetric cells in Comparative Example 2 and Examples 1-3.
[0026] Figure 6 2 is the nucleation overpotential of the two Zn||Zn symmetric batteries in Comparative Example 2 and Example 2.
[0027] Figure 7 The cyclic voltammograms of the two electrolytes in Comparative Example 6 and Example 7 are shown in FIG. Figure 7-1 is the cyclic voltammogram of the electrolyte of Example 7, Figure 7-2 This is the cyclic voltammogram of the electrolyte of Comparative Example 6.
[0028] Figure 8 It is the first cycle charge and discharge curve diagram of the two electrolytes in comparative example 6 and example 7.
[0029] Fig. 9 The coulombic efficiency and capacitance diagram of the two electrolytes in comparative example 6 and example 7.
[0030] Fig.10 The full battery of the two electrolytes in Comparative Example 6 and Example 7 at 0.2, 0.5, 1.0, 2.0Ag -1 Rate cycle diagram under current.
[0031] Fig.11 This is the XRD characterization test diagram of the materials in Comparative Example 2 and Example 2.
[0032] Fig.12 This is the XPS characterization test diagram of the materials in Comparative Example 2 and Example 2.
[0033] Fig.13 These are SEM characterization test images of the materials in Comparative Example 2 and Example 2.
[0034] Fig.14 This is a graph showing the cycle performance test results of the Zn||Zn symmetric battery in Comparative Example 7 and Example 2.
[0035] Fig.15 This is the result of the cycle test of zinc sulfate and zinc acetate electrolytes in the blue electricity system in Experiment 13. DETAILED DESCRIPTION
[0036] The present invention provides a zinc ion battery electrolyte composition, which contains zinc sulfate and hexamethylenetetramine. The present invention has been verified by experiments, and it has been confirmed that the electrolyte formed under the condition of compounding zinc sulfate and hexamethylenetetramine is used in zinc ion batteries, which can effectively improve various battery performances.
[0037] Furthermore, the present invention provides a zinc ion battery electrolyte based on the above electrolyte composition, which contains the above composition and a solvent.
[0038] In the electrolyte, the final concentration of zinc sulfate is 1-2 mol / L, and the final concentration of hexamethylenetetramine is 0.5-4 mg / mL. The electrolyte formed within this range is used to assemble zinc ion batteries, which can effectively overcome the corrosion of the metal zinc negative electrode and the uncontrollable dendrite growth that leads to poor battery cycle performance, low coulomb efficiency and even safety performance.
[0039] For example: in the electrolyte, the final concentration of zinc sulfate is 1 mol / L, and the final concentration of hexamethylenetetramine is 0.5 mg / mL. Or the final concentration of zinc sulfate is 1 mol / L, and the final concentration of hexamethylenetetramine is 1 mg / mL. Or the final concentration of zinc sulfate is 1 mol / L, and the final concentration of hexamethylenetetramine is 2 mg / mL. Or the final concentration of zinc sulfate is 1 mol / L, and the final concentration of hexamethylenetetramine is 4 mg / mL. Or the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 0.5 mg / mL. Or the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 1 mg / mL. Or the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 2 mg / mL. Or the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 4 mg / mL.
[0040] In the above combination, preferably, the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 1 mg / mL.
[0041] The preparation method of the zinc ion battery electrolyte comprises: preparing a zinc sulfate solution of a certain concentration by using a solvent; adding hexamethylenetetramine and mixing until it is completely dissolved.
[0042] The electrolytes involved in the following examples were prepared as follows:
[0043] (1) Weigh 14.387 g of zinc sulfate hexahydrate and use a 25 mL volumetric flask to make up to volume to prepare a blank ZnSO4 electrolyte with a concentration of 2 mol / L.
[0044] (2) 12.5 mg of hexamethylenetetramine (HMTA) was added to the blank electrolyte prepared in step (1), and the mixture was mixed and ultrasonicated until the hexamethylenetetramine was completely dissolved, thereby preparing a ZnSO4-0.5 mg / mL HMTA electrolyte with a concentration of 2 mol / L.
[0045] (3) Take 25 mg of hexamethylenetetramine (HMTA) and add it to the blank electrolyte prepared in step (1), mix and sonicate until the hexamethylenetetramine is completely dissolved, to prepare a ZnSO4-1 mg / mL HMTA electrolyte with a concentration of 2 mol / L.
[0046] (4) Take 50 mg of hexamethylenetetramine (HMTA) and add it to the blank electrolyte prepared in step (1), mix and sonicate until the hexamethylenetetramine is completely dissolved, to prepare a ZnSO4-2 mg / mL HMTA electrolyte with a concentration of 2 mol / L.
[0047] In addition, in the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0048] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, which are intended to explain the present invention rather than to limit it.
[0049] Example 1
[0050] Assembly of Zn||Zn symmetric battery with 2mol / L ZnSO4-0.5mg / mL HMTA as electrolyte
[0051] Weigh 14.387 g of zinc sulfate hexahydrate and 12.5 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZnSO4-0.5 mg / mLHMTA.
[0052] In the button CR2032 battery mold, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed from bottom to top. When installing the diaphragm, 80uL (2mol / L ZnSO4-0.5mg / mL HMTA) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0053] Example 2
[0054] Assembly of Zn||Zn symmetric battery with 2mol / L ZnSO4-1mg / mL HMTA as electrolyte
[0055] Weigh 14.387 g of zinc sulfate hexahydrate and 25 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare an electrolyte with a concentration of 2 mol / LZnSO4-1 mg / mL HMTA.
[0056] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL (2mol / L ZnSO4-1mg / mL HMTA) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0057] Example 3
[0058] Assembly of Zn||Zn symmetric battery with 2mol / L ZnSO4-2mg / mL HMTA as electrolyte
[0059] Weigh 14.387 g of zinc sulfate hexahydrate and 50 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare an electrolyte with a concentration of 2 mol / LZnSO4-1 mg / mL HMTA.
[0060] In the button CR2032 battery mold, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed from bottom to top. When installing the diaphragm, 80uL (2mol / L ZnSO4-2mg / mL HMTA) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0061] Example 4
[0062] Assemble stainless steel||stainless steel symmetric cell with 2mol / L ZnSO4-0.5mg / mL HMTA as electrolyte
[0063] Weigh 14.387 g of zinc sulfate hexahydrate and 12.5 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZnSO4-0.5 mg / mLHMTA.
[0064] In the button CR2032 battery mold, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed from bottom to top. When installing the diaphragm, 80uL (2mol / L ZnSO4-0.5mg / mL HMTA) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0065] Example 5
[0066] Assemble stainless steel||stainless steel symmetric cell with 2mol / L ZnSO4-1mg / mL HMTA as electrolyte
[0067] Weigh 14.387 g of zinc sulfate hexahydrate and 25 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare an electrolyte with a concentration of 2 mol / LZnSO4-1 mg / mL HMTA.
[0068] In the button CR2032 battery mold, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed from bottom to top. When installing the diaphragm, 80uL (2mol / L ZnSO4-0.5mg / mL HMTA) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0069] Example 6
[0070] Assemble stainless steel||stainless steel symmetric cell with 2mol / L ZnSO4-2mg / mL HMTA as electrolyte
[0071] Weigh 14.387 g of zinc sulfate hexahydrate and 50 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place the flask in a numerically controlled ultrasonic cleaner and perform ultrasonic treatment to completely dissolve the flask to prepare an electrolyte solution with a concentration of 2 mol / L ZnSO4-2 mg / mL HMTA.
[0072] In the button CR2032 battery mold, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed from bottom to top. When installing the diaphragm, 80uL (2mol / L ZnSO4-0.5mg / mL HMTA) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0073] Example 7
[0074] Assembly of Zn-V2O5 full battery with 2mol / L ZnSO4-1mg / mL HMTA as electrolyte
[0075] Vanadium pentoxide, conductive carbon black, and PVDF were mixed in a mass ratio of 7:2:1 and stirred for 12 hours to prepare a uniform electrode slurry, which was then coated on a stainless steel foil with a coating thickness of 15 μm. After condensation and drying for 24 hours, a positive electrode sheet was obtained. A solution with a concentration of 2 mol / L ZnSO4-1 mg / mL HMTA was then used as the electrolyte.
[0076] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the positive electrode sheet for preparing the positive electrode material, the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL of electrolyte (2mol / LZnSO4-1mg / mL HMTA) is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn-V2O5 full battery.
[0077] Comparative Example 1
[0078] Assemble the Zn||Zn symmetric battery with 1 mol / L ZnSO4 as electrolyte
[0079] Weigh 7.1935 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 1 mol / L.
[0080] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL (1mol / L ZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0081] Comparative Example 2
[0082] Assembling Zn||Zn symmetric battery with 2mol / L ZnSO4 as electrolyte
[0083] Weigh 14.387 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 2 mol / L.
[0084] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL (2mol / L ZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0085] Comparative Example 3
[0086] Assembling Zn||Zn symmetric battery with 3 mol / L ZnSO4 as electrolyte
[0087] Weigh 21.5805 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 3 mol / L.
[0088] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL (3mol / L ZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0089] Comparative Example 4
[0090] Assembling Zn||Zn symmetric battery with 4 mol / L ZnSO4 as electrolyte
[0091] Weigh 28.774 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 4 mol / L.
[0092] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL (4mol / L ZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.
[0093] Comparative Example 5
[0094] Assemble stainless steel with 2mol / L ZnSO4 as electrolyte || stainless steel symmetric battery
[0095] Weigh 14.387 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 2 mol / L.
[0096] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the stainless steel sheet with a diameter of 16mm (as the negative electrode), the diaphragm (Glass microfiber lilters) with a diameter of 16mm, the stainless steel sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL (2mol / L ZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery for testing ionic conductivity.
[0097] Comparative Example 6
[0098] Assembling a Zn-V2O5 full battery with 2 mol / L ZnSO4 as electrolyte
[0099] Vanadium pentoxide, conductive carbon black and PVDF were mixed in a mass ratio of 7:2:1 and stirred for 12 hours to prepare a uniform electrode slurry, which was then coated on a stainless steel foil and condensed and dried for 24 hours to obtain a positive electrode sheet. A solution with a concentration of 2 mol / L ZnSO4 was then used as the electrolyte.
[0100] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the positive electrode sheet for preparing the positive electrode material, the gasket, the spring sheet, and the positive electrode shell are placed in sequence. When installing the diaphragm, 80uL of electrolyte (2mol / LZnSO4) is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a full Zn-V2O5 battery.
[0101] Comparative Example 7
[0102] Assembly of a Zn||Zn symmetric battery with 2mol / L Zn(CH3COOH)2-1mg / mL HMTA as electrolyte
[0103] Weigh 10.978 g of zinc acetate dihydrate and 25 mg of hexamethylenetetramine, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZn(CH3COOH)2-1 mg / mLHMTA.
[0104] A Zn||Zn symmetrical battery was obtained by assembling in the manner of Example 2.
[0105] Performance test of the above case:
[0106] Experiment 1: Comparison of the cycling performance of Zn||Zn symmetric batteries in Examples 1 to 4
[0107] The four Zn||Zn symmetrical batteries obtained above were set to a charge and discharge current of 1.0 mA cm in a blue electric cycle system. -2 , with a fixed charge and discharge capacity of 1 mAh cm -2 The cycle performance test under the following conditions showed that the Zn||Zn symmetric battery showed the best cycle stability when the concentration of ZnSO4 electrolyte was 2 mol / L. When the concentration of ZnSO4 increased or decreased, its cycle performance was not as good as the cycle performance of 2 mol / L ZnSO4 as the electrolyte (Comparative Example 2).
[0108] Experiment 2: Comparison of Cycling Performance of Zn||Zn Symmetric Batteries of Comparative Example 2 and Examples 1 to 3
[0109] The four Zn||Zn symmetrical batteries obtained above were set to a charge and discharge current of 1.0 mA cm in a blue electric cycle system. -2 , with a fixed charge and discharge capacity of 1 mAh cm -2 The results of the cycle performance test under the conditions are as follows Figure 1 As shown by Figure 1 It can be seen that the Zn||Zn symmetric battery with a concentration of 2mol / L ZnSO4-1mg / mL HMTA electrolyte exhibits the best cycle stability, followed by the Zn||Zn symmetric battery with a concentration of 2mol / L ZnSO4-2mg / mL HMTA electrolyte, and then the Zn||Zn symmetric battery with a concentration of 2mol / LZnSO4-0.5mg / mL HMTA electrolyte. Its cycle performance first increases and then decreases with the increase of HMTA concentration. The reason may be that when the HMTA concentration in the electrolyte is insufficient, sufficient active sites cannot be formed to induce Zn 2+ The deposition of HMTA results in the inability to effectively inhibit the corrosion of the Zn negative electrode and the growth of Zn dendrites. When there is too much HMTA in the electrolyte, the conductivity of the solution is reduced due to its own non-conductivity, resulting in a decrease in the cycle performance.
[0110] Experiment 3: Comparison of the cycling performance of Zn||Zn symmetric batteries of Comparative Example 2 and Example 2 at different rates
[0111] The two Zn||Zn symmetrical batteries obtained above were placed in a blue electricity test system and the charge and discharge current was set to 1.0 mA cm -2 , with a fixed charge and discharge capacity of 1 mAh cm -2 The cycle performance test was carried out under the conditions with a charge and discharge current of 2.0 mA cm -2 , with a fixed charge and discharge capacity of 2 mAh cm -2 The cycle performance test was carried out under the conditions and the charge and discharge current was 4.0 mA cm-2 , with a fixed charge and discharge capacity of 4 mAh cm -2 The cycle performance test was carried out under the following conditions.
[0112] Test results such as Figure 2 As shown in the figure, it can be seen that no matter the current density is 1mA cm -2 , 2mA cm -2, Still 4mA cm -2 It can be clearly seen that the cycling performance of the Zn||Zn symmetric battery using 2mol / L ZnSO4-1mg / mL HMTA electrolyte is much higher than that of the blank control group electrolyte of 2mol / L ZnSO4.
[0113] Experiment 4: Test of ionic conductivity of stainless steel of comparative example 5 and examples 4 to 6 || stainless steel symmetric battery
[0114] The ionic conductivity of the four stainless steel||stainless steel symmetrical cells in the experimental group obtained above was tested in the electrochemical workstation chi660e with the low frequency set to 0.01 Hz, the high frequency set to 100000 Hz, and the initial voltage set to 0.01 V.
[0115] The results are as follows Figure 3 As shown by Figure 3 It can be seen that as the concentration of hexamethylenetetramine increases, its ionic conductivity decreases. This is because hexamethylenetetramine is non-conductive, which causes a slight decrease in the ionic conductivity of the electrolyte. Therefore, it is more appropriate to control the concentration of hexamethylenetetramine at about 1 mg / mL.
[0116] Experiment 5: AC impedance performance test of Zn||Zn symmetrical batteries of Comparative Example 2 and Examples 1 to 3
[0117] For the four Zn||Zn symmetrical batteries in the experimental group obtained above, the AC impedance was tested in the electrochemical workstation chi660e with the low frequency set to 0.01 Hz, the high frequency set to 100000 Hz and the initial voltage set to 0.01 V.
[0118] The test results are as follows Figure 4 As shown in Figure 2, as the concentration of hexamethylenetetramine increases, the AC impedance also increases, which is exactly the same as Figure 3 The ionic conductivity result is corresponding to that of hexamethylenetetramine, and the reason is that the non-conductivity of hexamethylenetetramine leads to an increase in impedance. The increase in impedance will cause a certain increase in the nucleation overpotential, which is beneficial to grain refinement and inhibiting dendrite growth, so the battery cycle time will be longer.
[0119] Experiment 6: Hydrogen evolution curve test of Zn||Zn symmetric battery of comparative example 2 and examples 1 to 3
[0120] The four Zn||Zn symmetric batteries obtained above were tested for hydrogen evolution curves in an electrochemical workstation chi660e with an initial voltage of -0.5V and a final voltage of 0.5V.
[0121] like Figure 5 As shown in the figure, with the increase of HMTA concentration in the electrolyte, the hydrogen evolution potential shifts to the negative direction, indicating that the addition of HMTA can inhibit the hydrogen evolution reaction, and when the HMTA concentration is 1 mg / mL, the inhibition of hydrogen evolution reaction is most obvious.
[0122] Experiment 7: Nucleation overpotential test of Zn||Zn symmetric battery of comparative example 2 and example 2
[0123] The electrolytes of the four Zn||Zn symmetric batteries obtained above were assembled according to the battery assembly method in Examples 1-4 to obtain Zn||Cu symmetric batteries, and the nucleation overpotential was tested using a blue electric system.
[0124] like Figure 6 As shown in the figure, with the addition of HMTA, its nucleation overpotential increases. A higher nucleation overpotential is conducive to the smaller grain size in the initial stage of zinc deposition, thus making Zn 2+ The deposition is more uniform. When using 2mol / LZnSO4 electrolyte, the nucleation overpotential is 32mV, while when using 2mol / LZnSO4-1mg / mLHMTA electrolyte, the nucleation overpotential is 51mV. This just shows that although the addition of HMTA reduces the ionic conductivity to a certain extent, it also increases the nucleation overpotential, which is beneficial to the grain refinement at the beginning of nucleation, making zinc deposition uniform and inhibiting dendrite growth.
[0125] Experiment 8: CV test of the full battery of Example 6 and Example 7
[0126] The full battery was tested on the chi660e electrochemical workstation, and the test results are as follows Figure 7 The figure shows the CV cyclic voltammogram of the full battery. It can be seen that the full battery using 2mol / L ZnSO4-1mg / mL HMTA electrolyte has a good overlap performance after 3 cycles in the figure, indicating that it has good electrochemical stability. Experiment 9: Constant current charge and discharge curves of the full battery of Comparative Example 6 and Example 7
[0127] like Figure 8 As shown in Figure 2, it can be observed that the initial discharge capacity of the full cell using 2 mol / L ZnSO4-1 mg / mL HMTA electrolyte is 280 mAh g -1 , higher than the 165 mAh g of blank electrolyte -1, which indicates that the reversibility of the full cell using 2mol / L ZnSO4-1mg / mL HMTA electrolyte is higher than that of the full cell with 2mol / LZnSO4 electrolyte.
[0128] Experiment 10: Long cycle performance diagram of full batteries of Comparative Example 6 and Example 7
[0129] Fig. 9 Shown in 2Ag -1 The long cycle performance of the complete battery tested under the conditions of 2 mol / L ZnSO4-1 mg / mL HMTA electrolyte is close to 100% coulombic efficiency, and the battery capacity is still maintained at 200 mAh g after 500 cycles. -1 The coulombic efficiency of the blank electrolyte was only close to 95%, and after 500 cycles, the battery capacity was only 60 mAh g -1 This shows that after using hexamethylenetetramine as an electrolyte additive, it has higher coulombic efficiency and battery capacity retention rate compared with blank electrolyte.
[0130] Experiment 11: Full-battery rate performance diagram of comparative example 6 and example 7
[0131] like Fig.10 As shown in Figure 2, it can be observed that the initial discharge capacity of the full cell using 2 mol / L ZnSO4-1 mg / mL HMTA electrolyte is 280 mAh g -1 , higher than the 165 mAh g of blank electrolyte -1 This indicates that the reversibility of the full cell using 2mol / LZnSO4-1mg / mL HMTA electrolyte is higher than that of the full cell with 2mol / LZnSO4 electrolyte.
[0132] Experiment 12: Characterization of Zn negative electrode before and after cycling of Zn||Zn symmetric battery of comparative example 2 and example 2
[0133] The batteries in Comparative Example 1 and Example 5 were disassembled before charging and discharging and after 3 cycles of charging and discharging reaction, and the zinc negative electrode was removed and rinsed with a large amount of anhydrous ethanol. After rinsing, they were placed in a vacuum drying oven and dried. The zinc negative electrode was used for material characterization test.
[0134] Fig.11The XRD tests were performed on the zinc negative electrode after 3 cycles of using 2mol / LZnSO4-1mg / mL HMT electrolyte, 3 cycles of using 2mol / L ZnSO4, and pure Zn foil. From the XRD characterization diagram, it can be seen that after 3 cycles, the characteristic XRD peak of Zn4SO4(OH)6·H2O has appeared on the surface of the zinc negative electrode circulating in the blank electrolyte. However, on the zinc negative electrode using hexamethylenetetramine electrolyte additive, the characteristic XRD peak belonging to Zn4SO4(OH)6·H2O is almost unobservable, indicating that the addition of HMTA inhibits the formation of Zn4SO4(OH)6·H2O by-products, that is, inhibits the corrosion of the Zn negative electrode. In order to further verify the effect of hexamethylenetetramine on the zinc negative electrode, the zinc negative electrode was circulated for 3 cycles in 2mol / LZnSO4-1mg / mL HMTA as the electrolyte, and then rinsed with ethanol for XPS test. Fig.12 As shown, it can be observed that the surface of the Zn negative electrode can be tested to contain C and N elements, and these two elements can only come from our hexamethylenetetramine additive, indicating that the addition of HMTA can in situ construct an interface molecular layer on the surface of the zinc negative electrode. Finally, the zinc negative electrode after the 2mol / LZnSO4 electrolyte and 2mol / LZnSO4-1mg / mL HMTA electrolyte cycle was subjected to SEM testing. The test results are shown in Fig.13 As shown in the figure, when we did not add hexamethylenetetramine, a large number of zinc dendrites were generated at the zinc negative electrode, while the zinc negative electrode with 2mol / LZnSO4-1mg / mL HMTA as the electrolyte was very smooth and basically no zinc dendrites were generated.
[0135] Experiment 13: Comparison of Cycling Performance of Zn||Zn Symmetric Batteries of Comparative Example 7 and Example 2
[0136] 1 mg / mL of hexamethylenetetramine electrolyte additive was added to both 2 mol / L ZnSO4 electrolyte and 2 mol / L Zn(CH3COOH)2 electrolyte. It can be observed that when the concentration of HMT added is the same, the cycle performance of 2 mol / L zinc sulfate + 1 mg / mL hexamethylenetetramine electrolyte additive can be cycled for more than 2000 hours, while the cycle performance of 2 mol / L zinc acetate + 1 mg / mL hexamethylenetetramine electrolyte additive can only be cycled for less than 500 hours. The results are as follows Fig.14 shown.
[0137] In addition, the present invention compares the performance of 2 mol / L ZnSO4 electrolyte and 2 mol / L Zn(CH3COOH)2 electrolyte. The performance determination method is as follows: 2 mol / L zinc sulfate and 2 mol / L zinc acetate are configured to perform a cycle test in a blue electricity system. The results are as follows: Fig.15 As shown in the figure, the performance of Zn negative electrode in 2mol / L ZnSO4 electrolyte is better than that of 2mol / L Zn(CH3COOH)2, but the cycle performance in these two electrolytes does not exceed 70 hours, which is much lower than the cycle hours of Zn negative electrode after compounding with hexamethylenetetramine electrolyte additive. This research result will help us to carry out more in-depth research on zinc ion battery electrolytes in the future.
[0138] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A zinc ion battery electrolyte, characterized in that: In the electrolyte, the final concentration of zinc sulfate is 2 mol / L, the final concentration of hexamethylenetetramine is 1-2 mg / mL, and the solvent is water.
2. A zinc ion battery electrolyte according to claim 1, characterized in that: In the electrolyte, the final concentration of zinc sulfate is 2 mol / L, and the final concentration of hexamethylenetetramine is 1 mg / mL.
3. The method for preparing the zinc ion battery electrolyte according to claim 1 or 2, wherein: include: A zinc sulfate solution of a certain concentration is prepared using a solvent; Add hexamethylenetetramine and mix until completely dissolved.
4. Application of the zinc ion battery electrolyte according to claim 1 or 2 or the zinc ion battery electrolyte obtained by the preparation method according to claim 3 in preparing a zinc ion battery.
5. A zinc ion battery, characterized in that: The battery comprises the zinc ion battery electrolyte according to claim 1 or 2 or the zinc ion battery electrolyte obtained by the preparation method according to claim 3.
Citation Information
Patent Citations
Zinc ion battery electrolyte and application thereof
CN115207494A